(untitled) (The Review of Diabetic Studies, 2024)
Healthcare-associated infections (HAIs) remain a major challenge across healthcare systems, demanding coordinated, interprofessional approaches that involve all clinical, diagnostic, and supportive departments. This integrative review examines the collective roles, responsibilities, and evidence-based contributions of multidisciplinary healthcare teams—including nursing, medicine, laboratory services, pharmacy, infection prevention units, environmental services, dentistry, radiology, rehabilitation, and administrative departments—in optimizing infection control outcomes. Literature published between 2016 and 2025 was systematically reviewed to identify collaborative strategies, departmental interactions, and organizational frameworks that support effective infection prevention. Findings indicate that unified workflows, shared protocols, cross-departmental communication, and integrated surveillance systems significantly reduce infection risks. Nursing remains central to frontline practices, while laboratories enhance diagnostic accuracy and early detection. Pharmacy supports antimicrobial stewardship, and environmental services provide essential sanitation measures. Administrative leadership fosters governance, resource allocation, and safety culture. The review highlights that infection control effectiveness increases when departments coordinate through structured communication pathways, shared training, and multidisciplinary team-based interventions. Recommendations include strengthening interprofessional education, integrating digital technologies, developing unified policy frameworks, and expanding real-time surveillance systems. Collectively, these strategies promote safer clinical environments and improved patient outcomes.